2017
DOI: 10.1016/j.canlet.2017.05.032
|View full text |Cite
|
Sign up to set email alerts
|

Detection of circulating tumor cells from cryopreserved human sarcoma peripheral blood mononuclear cells

Abstract: Circulating tumor cells (CTCs) enter the vasculature or lymphatic system after shedding from the primary tumor. CTCs may serve as “seed” cells for tumor metastasis. The utility of CTCs in clinical applications for sarcoma is not fully investigated, partly owing to the necessity for fresh blood samples and the lack of a CTC-specific antibody. To overcome these drawbacks, we developed a technique for sarcoma CTCs capture and detection using cryopreserved peripheral blood mononuclear cells (PBMCs) and our proprie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 30 publications
1
26
0
Order By: Relevance
“…Using a method based on isolation by size of tumor cells (ISET), Chinen et al [29] detected CTCs in sarcoma patients. More recently, Li et al [30] confirmed the detection of CTCs in cryopreserved human peripheral blood mononuclear cells and two studies analysing CTCs by FISH in small cohorts of osteosarcoma patients revealed a potential positive association between CTC count, disease progression and poor prognosis [31] , [32] . The present report is the first study investigating the regulation of CTC release after chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Using a method based on isolation by size of tumor cells (ISET), Chinen et al [29] detected CTCs in sarcoma patients. More recently, Li et al [30] confirmed the detection of CTCs in cryopreserved human peripheral blood mononuclear cells and two studies analysing CTCs by FISH in small cohorts of osteosarcoma patients revealed a potential positive association between CTC count, disease progression and poor prognosis [31] , [32] . The present report is the first study investigating the regulation of CTC release after chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Blood samples (15 mL) were collected from healthy donors. Peripheral blood mononuclear cells (PBMCs) were isolated according to a previous publication [ 13 ]. PBMCs were plated in three 6-well plates (1 × 10 6 cells/well) and incubated for 3 h in RPMI1640 (Gibco) supplemented with 1% (v/v) penicillin-streptomycin and 10% FBS in an incubator at 37°C and 5% CO 2 at 100% relative humidity.…”
Section: Methodsmentioning
confidence: 99%
“…In the future, postoperative surveillance strategies should be tailored to the specific histiotype given the differences in tumor biology and patterns of recurrence. The value of molecular surveillance with circulating tumor cells is also being investigated 257,258 …”
Section: Select Topicsmentioning
confidence: 99%